Sunday Under Three Heads - Dickens, Charles, 1812-1870 (Salt Lake City, UT : Project Gutenberg, 1997)
"Sunday Under Three Heads" by Charles Dickens is a social commentary published in the early Victorian period. This work is a satirical essay examining the societal attitudes toward Sunday leisure activities among the lower classes in England, challenging the moralistic views of the time regarding rest and recreation. Dickens argues that the efforts to impose strict Sabbath laws on the working class stem from a misunderstanding of their need for relaxation and enjoyment after a week of hard labor. In this book, Dickens presents a vivid depiction of Sunday life in London, contrasting the innocent joy of the working class seeking leisure with the hypocritical piety of the upper classes and the fanatical attitudes of certain religious figures. Through three distinct sections, he highlights the stark differences between the joy experienced by the poorer classes on their day off and the austere, often joyless atmosphere cultivated by the law and societal expectations. Dickens emphasizes the importance of allowing all individuals the right to enjoy their free time without unnecessary moral judgment, arguing for a more compassionate understanding of human nature and the need for joy in life. His advocacy for the acceptance of Sunday leisure serves as a criticism of the rigid and often oppressive nature of contemporary societal norms. (This is an automatically generated summary.)
As it is -- As Sabbath bills would make it -- As it might be made.
Release date is 1997-05-01
Transcribed from the 1905 Chapman & Hall edition (_The Works of Charles Dickens_, volume 28) by David Price
Keywords: England -- Social life and customs -- 19th century; Sunday